A field evaluation of the fungus Beauveria bassiana (Balsamo) for the control of litter beetle, Alphitobius diaperinus Panzer (Coleoptera : Tenebrionidae) in commercial broiler houses - Gumbi, Duma Petros (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.Agric.) -- University of Stellenbosch, 1999.